2005
DOI: 10.1007/s11120-004-6432-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of delayed chlorophyll a fluorescence registered in milliseconds time range

Abstract: Delayed fluorescence dark decays in the time interval from 0.35 to 5.5 ms are measured during dark to light adaptation in whole barley leaves and isolated thylakoid membranes, using a disc phosphoroscope. The changes in delayed fluorescence features are compared with variable chlorophyll fluorescence simultaneously registered with the same apparatus as well as in parallel by Handy PEA (Hansatech Instruments Ltd.), and absorbance changes at 820 nm. The registered delayed fluorescence signal is a sum of three co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 11 publications
3
62
0
Order By: Relevance
“…It was previously assumed that the time course of DF after the maximum (Figure 1) is possibly influenced by a number of dark photosynthetic processes (directly or indirectly modifying the characteristics of PSII) [13,14]. The decay of induction curve was generally explained by a decrease in the membrane energization as a result of secondary cation efflux from thylakoids [13,14]. Our results showed that half time of I decay-τ describe the level of interaction LR with dark processes of plants [10].…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…It was previously assumed that the time course of DF after the maximum (Figure 1) is possibly influenced by a number of dark photosynthetic processes (directly or indirectly modifying the characteristics of PSII) [13,14]. The decay of induction curve was generally explained by a decrease in the membrane energization as a result of secondary cation efflux from thylakoids [13,14]. Our results showed that half time of I decay-τ describe the level of interaction LR with dark processes of plants [10].…”
Section: Introductionsupporting
confidence: 52%
“…The incubation of detached leaves at 36℃ with further more notable moisture loss resulted in I decline as opposed to variants with other thermal treatment ( Tables 1-3, r IM(T) at incubation of 400 min). I depends on the size of ECP on a membrane [11,13,14] donor availability [11][12][13], as well as possible concentration of active PS II [10]. Our results have shown that half time of I decay-τ describe the level of interaction LR with dark processes of plants [10].…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations